The effects of inflation, shortages, and partial backlogs on products that deteriorate over time in response to varied demand - Raghav, Yashpal Singh; Ali, Mohd Aftab; Goel, Abhinav; Kumar, Sandeep (Brazilian Journal of Biometrics, 2024)
This study aims to determine an optimal policy to deal with a situation where a retailer should have enough stock to meet customer demands and prevent supply loss and deterioration. In this study, we demonstrate the impact of partial backlogging, shortages, and inflation on decaying items to provide the most relevant solutions to this problem. The model uses a two-parameter Weibull deterioration distribution with an exponential demand rate. Numerical results and sensitivity analysis are combined with a graphical demonstration, and the proposed approach is reliable and accurate, providing a new explanation for a different type of system. This paper determines the total cost and optimal production run time by developing an inventory model. Sensitivity analysis is carried out to demonstrate the proposed model.